The Common Chanterelles (Cantharellus and Craterellus) of Florida - Kaori Hall; Benjamin Lemmond; Matthew E. Smith (EDIS)
This document is intended to introduce the general public to the chanterelle mushrooms of Florida and includes a preliminary key to Florida’s most common chanterelle species. Written by Kaori Hall, Ben Lemmond, and Matthew E. Smith, and published by the UF/IFAS Plant Pathology Department, February 2023.